Ethical dilemmas in call centres: how to survive in the modern sweatshops?. (17th July 2012) - Csillag, Sara; Takacs, Sandor; Kiss, Csaba; Szilas, Roland
In this paper, we attempt to discover links between emotional labour and ethical challenges at the bottom of the hierarchy based on a research project in a utility company's customer services department. Based on 80 in depth interviews, we also investigate and identify those narratives and tactics that the customer service employees use in order to cope with ethical problems and emotional labour, on individual and on group level. Finally, we outline some of the possible leadership patterns connected to reducing emotional burden, reframing the situation and practicing moral imagination as a potential way out of the 'emotional and ethical trap'.